Factors Affecting the Earnings Response Coefficient : Evidence in Indonesia - Nurhaliza; Naz'aina; Yunina (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This study aims to analyze the effect of corporate social responsibility disclosure, growth opportunities, and firm size on the earnings response coefficient in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. This research is a quantitative study using panel balance data that collected using documentation techniques obtained through the website www.idx.co.id and the official website of each company. This study used multiple linear regression panel data with the Eviews 12. There were 141 manufacturing companies with a purposive sampling technique. The results show that corporate social responsibility disclosure has a positive and significant effect on the earnings response coefficient. This indicates that increase corporate social responsibility disclosure would lead to increase the earnings respon coefficient. The growth opportunities has negative insignificant effect on the earnings response coefficient and firm size has positive insignificant on the earnings response coefficient. The negative coefficient implies that higher growth opportunity lead to decreases earnings respon coefficient .